Vulneración del interés superior del menor, al momento que el progenitor tenedor, obstaculiza el régimen de visitas - Olaya Montoya, Martha Beatriz (2015)
This thesis entitled "Violation of the interests of the child, when the parent fork hinders visitation", its development is essential because at present the minors are being affected in their psychological integrity because their parents retaliatory their divorce or separation, limited to the visitor parent to see your child achieve, not being at home the day and time designated by the judge so that they comply with the visitation; This obstacle must be checked and repressed fork parent violates the interests of the minor and the emotional state of the child and of his father fails to see and maintaining family relationships. This becomes necessary that the rights of the minor and the parent visitors are guaranteed, remain relevant include a reform of the Organic Code of Children and Adolescents. The theoretical and field work of this thesis has allowed me to get criteria, with clear and precise grounds of well known literature, which contributed to the verification of targets, and testing of the hypotheses, allowing support changes to the Organic Law Childhood and Adolescence, prior to ensure the best interests of the child and adolescent is being limited to his father to visit without obstacles by its parent that leaves you visit the child. The content of this thesis is an intellectual effort in the scientific and methodological level, which deals theoretically and empirically, the limitation on the right to visits from parent to child. Such limitations on visitation by the holder hampering moving the child to another place so that the father can not see and engage in family relations visit